Environmental Risk Factors of Psychosis: A Review - Jagieła, Bartosz; Bolek, Michał; Fidyk, Monika; Kędzia, Aleksandra; Musialska, Dominika; Minkiewicz, Magda (Quality in Sport, 2025)
Psychosis is a severe mental health condition that can be debilitating for a person’s well-being. It is characterized by disturbances in perception, emotional regulation and thought processes, including symptoms like hallucinations and delusions, leading to a disconnection from reality. Patients often suffer when trying to meet the demands of ordinary life. Genetic predisposition plays a significant role in development of psychosis. Besides these, there are also environmental influences, which contribute as a trigger and later progression of psychotic disorders. These external determinants could possibly be managed in attempts to contain the problem of increased mental health conditions with the main psychotic component. This article reviews the literature reports of current environmental risk factors of psychosis. The keyword used was “psychosis” searched alone or in combination with “risk factors”, “environmental factors” or “external factors”.